2019
DOI: 10.1093/nar/gkz214
|View full text |Cite
|
Sign up to set email alerts
|

Differential uptake, kinetics and mechanisms of intracellular trafficking of next-generation antisense oligonucleotides across human cancer cell lines

Abstract: Antisense oligonucleotides (ASOs) modulate cellular target gene expression through direct binding to complementary RNA. Advances in ASO chemistry have led to the development of phosphorothioate (PS) ASOs with constrained-ethyl modifications (cEt). These next-generation cEt-ASOs can enter cells without transfection reagents. Factors involved in intracellular uptake and trafficking of cEt-ASOs leading to successful target knockdown are highly complex and not yet fully understood. AZD4785 is a potent and selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 46 publications
8
74
0
1
Order By: Relevance
“…3b) highlighting the protective effect that results from macrocyclization. To assess the cell penetration properties of unlabelled analogues, we determined their cytoplasmic and nuclear concentrations using a mass spectrometry-based methodology [25][26][27] and the Tat peptide as reference. RKO cells were incubated (c(peptide) = 25 µM) for 90 min and 24 h, then the cells were lysed and fractionated to isolate cytoplasmic and nuclear contents for subsequent UPLC-MS analysis.…”
Section: Helix α3mentioning
confidence: 99%
“…3b) highlighting the protective effect that results from macrocyclization. To assess the cell penetration properties of unlabelled analogues, we determined their cytoplasmic and nuclear concentrations using a mass spectrometry-based methodology [25][26][27] and the Tat peptide as reference. RKO cells were incubated (c(peptide) = 25 µM) for 90 min and 24 h, then the cells were lysed and fractionated to isolate cytoplasmic and nuclear contents for subsequent UPLC-MS analysis.…”
Section: Helix α3mentioning
confidence: 99%
“…The fluorescence from the secondary antibody is detected by fluorescence microscopy, and fluorescence can be quantitated to measure the relative amount of internalized oligonucleotide. Additional co-localization studies with membrane proteins involved in endocytosis can aid in the study of subcellular localization ( 44 , 105 , 107 ). Immunofluorescence assays can be performed using unlabeled oligonucleotides, and the use of antibodies for detection renders this method highly specific.…”
Section: Discussionmentioning
confidence: 99%
“…While NMR-based quantitation suffers from a lack of sensitivity, mass spectrometry methods are notable for their excellent sensitivity. Mass spectrometry methods are becoming more and more common for measuring the total cellular uptake of RNA therapeutics, both in cultured cells and ex vivo ( 42 , 107 , 116–119 ). Cells or tissues are homogenized and lysed, and the cleared lysates are analyzed by liquid chromatography and mass spectrometry (LC–MS, Figure 4C ) ( 42 , 107 , 116–119 ).…”
Section: Discussionmentioning
confidence: 99%
“…AZD4785 was previously shown to efficiently deplete KRAS and was associated with an antitumor effect in mice (Ross et al, 2017;Sacco et al, 2019). In addition, cellular trafficking and localization of AZD4785 across different tumor cell lines have been characterized and was found to vary (Linnane et al, 2019). Following completion of a phase I trial the molecule was demonstrated to be safe and well-tolerated, but it was discontinued by AstraZeneca because of its insufficient efficacy possibly due to targeting both mutant and wild-type KRAS mRNA (Yang et al, 2019).…”
Section: Azd4785mentioning
confidence: 99%